UNFORSEEN HEALTH PROBLEM IN FEMALE SEASONAL AGRICULTURAL WORKERS: URINARY INCONTINENCE - Kılıçlı, Ayşegül; Koruk, Fatma (LIFE: International Journal of Health and Life-Sciences, 2018)
Female seasonal agricultural workers constitute a risk group in terms of urinary incontinence because such workers have trouble in accessing and using health care services due to their working conditions and their low socio-economic levels. The study was carried out to determine the prevalence of urinary incontinence and factors affecting these and treatment received in female seasonal agricultural workers. In this cross-sectional study in which 300 women were reached. 56.0% of the women have urinary incontinence. The risk of having urinary incontinence is increased 3.5 times by being married, 6.7 times by having a chronic cough, 2.9 times by having a cystocele. Only 26.2% of the women had sought help from a healthcare organization with complaints of urinary incontinence. According to the study there was urinary incontinence in more than half of the women, but it was determined that the women made little effort to receive treatment for their urinary incontinence. It is recommended that women should be educated in topics like UI statistics, risk factors and the prevention and treatment of UI, and that those who have incontinence should be guided to receive treatment.